Effect of cation structure of tetraalkylammonium- and imidazolium-based ionic liquids on their conductivity. (20th February 2019) - Arkhipova, Ekaterina A.; Ivanov, Anton S.; Maslakov, Konstantin I.; Savilov, Serguei V.; Lunin, Valery V.
Abstract: Electrical conductivities of pure tetraalkylammonium- (N + Me4, N + Et4, N + Bu4, N + Me3 Hex) and imidazolium- (EMIM +, BMIM + ) based ionic liquids (ILs) with bis(trifluoromethylsulfonyl)imide (TFSI − ) anion and their acetonitrile solutions were measured in two temperature ranges of 298–368 and 298–348 K. Acetonitrile was used as an organic solvent to decrease the viscosity of ILs and, therefore, to increase the mobility of charge carriers. The maximum conductivity of acetonitrile solutions of both tetraalkylammonium- and imidazolium-based ILs was found to decrease with cation size. The conductivity – temperature dependencies of pure ILs and their acetonitrile solutions were analyzed using three approaches based on the Arrhenius equation for non-associating electrolytes, the Vogel-Fulcher-Tammann equation for ionic conductivity of glass-forming liquids and the Litovitz equation for associated liquids. The dilution of ILs with acetonitrile significantly reduced their activation energies of conductivity. At the same time, the activation energy decreased with increasing the alkyl chain length because of the deceleration of the ion transfer and the growth of the viscosity. Graphical abstract: Image 1 Highlights: Electrical conductivities of two classes of ionic liquids were measured. Activation energies of conductivity were calculated using the Arrhenius, Vogel-Fulcher-Tammann and Litovitz equations. Electrical conductivity and its activation energy depend on the alkyl chain length of IL.